Corporate Accounting and the Law - Edward M. Bullard (Washington University Law Quarterly, 1953)
The corporate abuses and financial excesses of the 1920’s showed the need for stricter statutory and accounting control over numerous corporate practices. Since 1930 the legislatures of practically all of the states have either adopted entirely new corporation acts or have substantially amended the existing acts. Unfortunately there is much less uniformity among these new laws than might have been hoped for, either as to the abuses dealt with or as to the methods adopted for curing them. Furthermore, while some awareness of accounting principles here and there is evidenced, by and large relatively little consistent accounting theory manifests itself. It goes without saying that accounting requirements can never cut below statutory minimum requirements but as a practical matter it is seldom that a statutory provision will be found to be more restrictive than the accounting rule. On the contrary, a corporation or its counsel, when the accountants are called in, may be rudely awakened to the fact that things are not what they legally seem and that the accounting policy involved is something quite different from the legislative policy. Although the several matters hereinafter discussed bear, for the most part, no necessary relationship with one another, all of them involve problems of practical present-day application and, moreover, problems the answers to which are by no means wholly settled as to either their legal or accounting aspects.
Keywords: Accounting